(untitled) (Bangladesh Journal of Medical Science, 2019)
Notably, reproductive technology and its applications in human subject are not only debatable ethically but also religiously, where objections are raised by the contemporary scholars and specialists of the field on CRISPR Cas-9 due to its potential application for the genome editing. This does however generated a dialogue both in religion and modern ethico-legal world regime. Some contemporary bioethicists are of the view that this technology is one of those issues which have the most complex ethical concerns, fearing that this technology could transforms with the expectations and ambitions about human control over the biological world. Consequently, this is an area of anxiety not only for the bioethicists but also for the theologians. Thus it needs proper investigation, as it is not solely a scientific innovation, but in fact an ethical, legal and biomedical issue. Bangladesh Journal of Medical Science Vol.19(1) 2020 p.11-16